Active Food Packaging from Alginate-Based Film Containing Onion Peel Extract (Allium cepa) - Amran, Farah Izzati Shamimi; Zamri, Amir Izzwan; Arifin, Heni Radiani; Shafrina, Azlin-Hasim (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
Consumers wanting safe and eco-friendly food packaging have led to better active packaging materials. Alginate is a polysaccharide extracted from seaweed and has the potential to be considered a promising material for packaging applications; however, its application is limited due to poor mechanical properties and high water vapor (WVP). The mechanical and barrier properties can be altered by adding or blending with other materials, such as the incorporation of bioactive compounds from onion peel extract (Allium Cepa). This study was designed to extract onion peel and test its antioxidant and antimicrobial activities; alginate-based film incorporated different concentrations of onion peel extract (12.5%, 25%, and 50%) (w/v) and determined its antioxidant or antimicrobial activity and physicochemical properties. Results demonstrated that the onion peel extract and alginate-based films containing onion peel extract show antioxidant activity; however, no antimicrobial activity was detected. When the concentration of onion peel extract (Allium Cepa) in alginate-based film increased, it significantly improved the alginate-based film’s mechanical properties, colour, solubility, and biodegradability. However, the water vapour permeability was reduced by increasing the onion peel extract. In conclusion, adding onion peel extract improved the antioxidant activity, colour, mechanical strength, solubility, and biodegradability characteristics of alginate-based films compared to control. Hence, this film has the potential to be used as active packaging.